Comparative genomic hybridisation in malignant deciduoid mesothelioma. Issue 7 (28th March 2006) - Scattone, A; Pennella, A; Gentile, M; Musti, M; Nazzaro, P; Buonadonna, A L; Marzullo, A; Cavone, D; Pollice, L; Serio, G
Abstract : Background: Malignant deciduoid mesothelioma is a rare variant of epithelioid mesothelioma. This tumour generally has poor prognosis, and can be asbestos related. Aim: To identify peculiar genetic changes responsible for critical phases in pathogenesis of malignant deciduoid mesothelioma and their prognostic relevance. Methods: Comparative genomic hybridisation was carried out in six cases of malignant pleural deciduoid mesothelioma, four sporadic and two familial. All cases were found to be asbestos related. Four patients died during follow-up and the mean survival was 29.5 (SD 14.2, range 12–43) months. Results: Genetic abnormalities were found in all the tumour tissues, the most frequent being chromosomal gains at 1p, 12q, 17, 8q, 19 and 20 and losses at 13q, 6q and 9p. Survival was found to be longer in those patients who presented a smaller number of losses (⩽2) in the tumorous chromosomes. Conclusions: Although numerous genetic changes are presented by deciduoid mesotheliomas, certain chromosomal regions are preferentially affected. The clinical outcome for this mesothelioma subtype is predicted by the number of losses.